Safety and feasibility assessment of biodegradable poly (l-lactic acid/ε-caprolactone) membrane for guided bone regeneration: A case series of first-in-human pilot study - Kinuko Ogata; Seigo Ohba; Yoshinori Sumita; Izumi Ashahina (Elsevier, 2022)
Background/purpose: Guided bone regeneration (GBR) is the most popular technique for alveolar ridge augmentation in implant dentistry, and resorbable cell barrier membrane, made of collagen, is widely used. We tried to develop a new resorbable cell barrier membrane from an animal-free product. This study aimed to investigate the safety and feasibility for clinical application of poly (l-lactic acid/ε-caprolactone) [P (LA/CL)] membrane, a novel biodegradable synthetic material used for GBR. Materials and methods: Patients who required horizontal bone augmentation (≥3 mm implant exposure) for implant treatment were included in the study. P (LA/CL) membrane was used simultaneously with implant placement to achieve bone augmentation by GBR. The occurrence of adverse events was assessed until the follow-up period of a second surgical procedure. The amount of bone augmentation was assessed by means of cone-beam computed tomography, and implant stability was assessed by measuring the implant stability quotient (ISQ). Student's t-test was used and the level of significance was set at p < 0.05. Results: This first-in-human study comprised five participants. Adverse events were observed in three of five patients, and a cause-and-effect relationship of the membrane could not be denied in one of them. Good bone formation was observed in the GBR region of all five patients. The ISQ during the second surgical procedure indicated good osseointegration in all the patients. Conclusion: The application of P (LA/CL) membrane for bone augmentation with GBR made it possible to maintain the augmented bone volume without causing any irreversible adverse events. However, further investigations on humans are required to confirm the safety of this biomaterial.